2020
DOI: 10.1186/s12888-020-2455-2
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between dietary patterns and depression mediated by serum levels of Folate and vitamin B12

Abstract: Background: Major depressive disorder is among main worldwide causes of disability. The low medication compliance rates in depressed patients as well as the high recurrence rate of the disease can bring up the nutrition-related factors as a potential preventive or treatment agent for depression. The aim of this study was to investigate the association between dietary patterns and depression via the intermediary role of the serum folate and vitamin B12, total homocysteine, tryptophan, and tryptophan/competing a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 39 publications
3
43
0
1
Order By: Relevance
“…Homocysteine (HCy) is a non-proteinogenic sulfurated amino acid [47]. No differences in HCy levels in depressed adult patients and healthy individuals [47][48][49][50] or an association between HCy and DD were observed [47]. The increased risk of depression was reported only in older adults with a high HCy level [30].…”
Section: Discussionmentioning
confidence: 99%
“…Homocysteine (HCy) is a non-proteinogenic sulfurated amino acid [47]. No differences in HCy levels in depressed adult patients and healthy individuals [47][48][49][50] or an association between HCy and DD were observed [47]. The increased risk of depression was reported only in older adults with a high HCy level [30].…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation of antidepressants with folate and/or vitamin B12 in one study reduced the risk of relapse after successful remission [ 172 ]. Not all studies, however, have found an association between homocysteine and depression [ 174 , 175 , 176 , 177 , 178 , 179 ]. The population-based Rotterdam Study found an association between depression and homocysteine; however, the association was reduced after controlling for cardiovascular disease and functional disability [ 152 ].…”
Section: Methodsmentioning
confidence: 99%
“…healthy " dietary pattern characterized by high intakes of phytochemical rich foods including fruits, vegetables, medium fat dairy, nuts, legumes and sh was protectively associated with depression and anxiety (22,25). In addition, some other studies con rmed the health bene t effects of DPI on abdominal obesity, lipid pro le and insulin resistant (13,14).…”
Section: Discussionmentioning
confidence: 96%
“…Fruits and vegetable are main sources of folate. Results of some studies shown that there are association between serum folate and dietary intake of this vitamin and depression (25,32,33). It can be effect on mental health via methylation in the nervous system (32).…”
Section: Discussionmentioning
confidence: 99%